Management of respiratory symptoms in paediatric palliative care. Issue 3 (September 2015) - Craig, Finella; Henderson, Ellen M.; Bluebond-Langner, Myra
<x xml:space="preserve">Abstract</x> Purpose of review Respiratory symptoms in children with life-limiting and life-threatening conditions are common, distressing and have a lasting impact, yet there is a paucity of evidence to guide clinicians in their management. This article makes a series of recommendations for the management of the most frequent and distressing respiratory symptoms encountered in paediatrics (dyspnoea, cough, haemoptysis and retained secretions) with attention to the evidence from research. Recent findings There are very few paediatric studies exploring any aspect of respiratory symptoms in paediatric palliative care, so much of the evidence base has been drawn from adult studies, few of which have been published in the past 12–18 months. Summary In the absence of well designed paediatric studies we need to judiciously apply what we can extrapolate from adult studies to each child we are treating; selecting interventions and approaches carefully, adjusting them when there is no evidence of individual benefit.